สมบัติทางกายภาพของวัสดุเชิงประกอบพอลิโอเลฟินส์และถ่านไม้ไผ่ - วรวัฒน์ สุธรรมน้อย (จุฬาลงกรณ์มหาวิทยาลัย, 2007)
Two kinds of polyolefins/bamboo charcoal composites were studied in their physical properties. One is polypropylene (PP)/bamboo charcoal composites and the other is low density polyethylene (LDPE)/bamboo charcoal composites. The amount of bamboo charcoal added in the composite materials were 5, 10, 15, 20 phr. Polyolefins/bamboo charcoal composites were prepared by using two different processes of mixing and then formed the composited material by using compressing method. The first process of mixing polyolefin and bamboo charcoal was to use only two-roll mill, the second process of mixing polyolefin and bamboo charcoal was to use both internal mixer and two-roll mill. According to results of mechanical properties, it could be concluded that the mixing process by using both of internal mixer and two-roll mill provided the better results of mechanical properties than those obtained from only two-roll mill mixing process. Tensile strength and modulus increased and elongation at break decreased, while the amount of bamboo charcoal in the composite materials increased. The tensile strength of PP/bamboo charcoal composites was better than that of original polypropylene but the tensile strength of LDPE/bamboo charcoal composites was a little bit lower than that of LDPE. In addition, water absorption of polyolefins/bamboo charcoal material was much better than those of original polyolefins. Electrical resistance of polyolefins/bamboo charcoal materials decreased comparing with that of pure PP and LDPE.